Elements of pedagogical support of professional orientation of adolescents - Failun Firievna Grigoryan (Вестник Майкопского государственного технологического университета)
In the article the author points that in the coming years competition is expected in the market of educational services, and, above all, in the work of universities. These problems create difficulties for young people in choosing their future professional orientation. In order to address these and other issues, it becomes necessary to create a special educational exchange that serves as a tool for implementing a professional educational trajectory and imposes high requirements on the process of forming scientific and theoretical foundations of the study in the context of a professional educational route. Despite the fact that the attention of practical scientists and theorists to the problems of professional self-determination of young people is increasing, nevertheless, the effectiveness of vocational guidance work by educational organizations remains insufficiently investigated. The principles, components and tasks determining the success of their professional choice are presented by the author as elements of pedagogical support of adolescents. Diagnostics of professional preferences of adolescents can be realized through self-awareness, which provides for the study of adolescents' individual personality traits as part of a particular profession, as well as by assessing individual abilities, diagnosing professionally important personal qualities and their level of expression. Thus, the pedagogical support elements considered by the author will determine the success of adolescents' professional choice, namely, to acquire readiness for self-education, self-development, designing their own line of conduct, mastering high technologies, complex integrated knowledge, relevant competences, etc.